TOWARDS COHESION IN DISABILITY RESEARCH - Penn, Claire; Watermeyer, Jennifer; Barratt, Joanne (PINS-Psychology in Society, 2025)
Watermeyer, B, Swartz, L, Lorenzo, T, Schneider, M & Priestley, M (eds) (2006) Disability and social change: A South African agenda. Cape Town: HSRC Press. ISBN 0-7969-2137-7 pbk. Pages xii + 417. There is no shortage of disability in South Africa. It is ever-present and profoundly linked to our historic past, and to issues of social inequity, poverty and lack of resources. There is however an acute shortage of writings about disability in South Africa and this shortage of writing has the potential to reflect negatively on the disability movement and to jeopardize appropriate access and resource distribution. Further without proper sustained scientific research in this area, development of appropriate policy and suitable approaches to prevention and effective service delivery will not happen.